Hydrogel adhesive and preparation method thereof, negative electrode and battery
Through the combination of flexible hydrogel adhesive and Si-based particles, a chain-entangled foam structure with high mechanical strength and conductivity is formed, which solves the problem of volume expansion and poor conductivity of silicon-based negative electrodes, and improves the circulation of lithium-ion batteries. Lifespan and stability, and reduce environmental pollution and production costs.
Patent Information
- Application Number
- CN202411378313.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
The silicon-based anode has poor cycle life and rate performance due to volume expansion and poor conductivity in lithium-ion batteries, which limits its commercial applications.
Using flexible hydrogel adhesives, including flexible hydrogel polymers, alginate polymers and self-healing polymers, combine with Si-based particles through chain tangled foam structures to form high mechanical strength and conductivity negative electrode.
It effectively solves the volume expansion problem of Si-based negative electrode, improves the cycle life and cycle stability of the battery, and reduces environmental pollution and production costs due to the use of green and pollution-free hydrogel adhesives.
Smart Images

Figure CN119242253A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a hydrogel adhesive, a preparation method thereof, a negative electrode, and a battery. Background Art
[0002] Silicon (Si), as one of the current candidate negative electrodes, can significantly improve the energy density of lithium-ion batteries (LIBs) and meet the long-term operation of high-power instruments. Because silicon has an ultra-high theoretical specific capacity (Li 15 Si4 is 3200 mAh g -1 ) and a low lithium deintercalation potential (compared with Li / Li + is 0.4 V). However, the huge volume change of more than 300% during the silicon alloying / dealloying phase transformation leads to cracking, pulverization, and peeling of the silicon-based negative electrode, ultimately causing a serious decline in the battery capacity and severely hindering its commercial application in lithium batteries. Therefore, SiO x (0 < x < 2) has a compromise theoretical lithium storage capacity (1800 - 2500 mAh g -1 ) and a longer cycle life, and has been proven to be the most promising choice among silicon-based candidate materials. Although inert components such as lithium silicate and Li2O are formed during the initial lithiation process of SiO x , they remain on the periphery of Si, forming a stable solid electrolyte interface (SEI) layer and buffering the volume effect. Unfortunately, so far, the SiO x negative electrode still cannot achieve long cycle performance and ideal rate performance, mainly due to the still-existing volume expansion (about 200%) and its poor conductivity.
[0003] Conductive hydrogels (ECHs) have been considered a viable strategy to solve the two major problems of SiO x . High-performance flexible hydrogels are expected to have excellent mechanical strength, simple synthesis procedures, good fatigue resistance, and good biocompatibility. Hydrogels with a three-dimensional cross-linked porous microstructure have become one of the most promising candidates due to their similarity to natural tissues, excellent flexibility, biocompatibility, and self-healing ability.
[0004] Can be used to develop hydrogels with ECHs, usually based on hydrophilic polymers such as polyvinyl alcohol (PVA), polyacrylamide (PAM) or polyacrylic acid (PAA), with inherently tunable mechanical properties and excellent biocompatibility. Among various conductive fillers, conductive polymers CPs with specific π-conjugated systems: such as polyaniline (PANI), polypyrrole (PPy) and poly (3,4-ethylenedioxythiophene) (PEDOT) have high conductivity, good mechanical properties, easy processability and extraordinary biocompatibility, making them the best choice for constructing hydrogels with three-dimensional cross-linked porous microstructures. The unique organic and polymeric structures of conductive polymers have a variety of chemical modification sites that can be integrated with the hydrophilic hydrogel network to pave uniformly dispersed conductive pathways. Doping methods based on CPs can introduce cross-linking, steric effects and self-assembly capabilities using multifunctional cross-linkers such as phytic acid, carbon dots or borax, thereby releasing new functions to regulate morphology and physical / chemical properties. However, conductive polymer chains are usually rigid and hydrophobic, which may lead to structural inhomogeneity and aggregation, thereby destroying the electron transport path and resulting in poor battery performance.
[0005] To this end, the present application provides a hydrogel adhesive and a preparation method thereof, a negative electrode, and a battery. Summary of the invention
[0006] The present application provides a hydrogel adhesive and a preparation method thereof, a negative electrode, and a battery. The hydrogel adhesive has a chain entanglement foam structure, which can effectively solve the expansion problem of Si-based negative electrodes and improve the battery cycle life and cycle stability.
[0007] The technical solution adopted by this application to solve its technical problem is:
[0008] In a first aspect, the present application provides a hydrogel adhesive comprising the following raw materials: a flexible hydrogel polymer, an alginate polymer, and a self-healing polymer, wherein the weight ratio of the flexible hydrogel polymer, the alginate polymer, and the self-healing polymer is (3.2-3.5):1:(3.2-3.5).
[0009] In some embodiments, the flexible hydrogel polymer includes any one or more of polyaniline, polypyrrole, and poly(3,4-ethylenedioxythiophene).
[0010] In some embodiments, the alginate polymer includes any one or any combination of laminaria gum, alginate, alginate and carboxymethyl cellulose salt.
[0011] In some embodiments, the self-healing polymer is polyacrylic acid.
[0012] In a second aspect, a method for preparing a hydrogel adhesive comprises the following steps:
[0013] The flexible hydrogel polymer, the alginate polymer and the self-healing polymer are mixed according to the weight ratio, and a solvent and a cross-linking agent are added to react. After the reaction is completed, a hydrogel adhesive is obtained.
[0014] In a third aspect, the present application provides a negative electrode, comprising the hydrogel adhesive described above.
[0015] In a fourth aspect, the present application provides a method for preparing the negative electrode, comprising the following steps:
[0016] The hydrogel binder, Si-based particles and conductive agent are fully mixed to obtain Si-based negative electrode slurry;
[0017] The Si-based negative electrode slurry is coated on the rough surface of the Cu foil and dried to obtain the negative electrode.
[0018] In some embodiments, the drying is first drying at 60° C. for 2 h, and then vacuum drying at 120° C. for 12 h.
[0019] In some embodiments, the particle size of the Si-based particles is 2-3 μm; the mass ratio of the Si-based particles, the conductive agent and the adhesive is 15:3:2.
[0020] In a fifth aspect, the present application provides a lithium-ion battery comprising the negative electrode described above.
[0021] The beneficial effects of this application are:
[0022] 1. The hydrogel adhesive described in the present application has a chain entangled foam structure, which can effectively solve the expansion problem of Si-based negative electrodes and improve the battery cycle life and cycle stability.
[0023] 2. The preparation method of the hydrogel adhesive used in the present application is to synthesize a new type of chain entanglement adhesive by a simple physical and chemical method from a high-performance flexible hydrogel, an alginate polymer and a self-healing polymer. This simple production process is conducive to the large-scale production of the adhesive with the chain entanglement foam structure, and the conductive hydrogel has excellent mechanical strength, simple synthesis process, good fatigue resistance and good biocompatibility;
[0024] Moreover, the highly elastic polymer network formed by the chain entanglement foam hydrogel can effectively solve the huge physical stress problems caused by the poor conductivity and volume expansion of SiOx itself.
[0025] 3. The hydrogel adhesive described in the present application uses an organic water-based polymer as an adhesive, which has the advantages of low cost, simple preparation and abundant resources. In addition, as a type of green and pollution-free adhesive material, the hydrogel adhesive can avoid the toxicity and pollution caused by fluorine-containing adhesives, greatly reduce environmental pollution, and greatly reduce the cost of purifying the environment.
[0026] 4. The hydrogel adhesive described in the present application has good adhesion, which greatly ensures the integrity of the electrode structure and avoids the physical stress problem caused by the volume expansion of the Si base. Furthermore, the chain entanglement foam adhesive further improves the cycle stability of the battery by forming a strong intermolecular force on the Si base surface, which can greatly extend the battery life.
[0027] 5. The preparation method of the negative electrode described in the present application adopts simple mechanical grinding and traditional coating method, and uses a hydrogel adhesive to prepare the electrode sheet, which is conducive to the large-scale production of SiOx negative electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0029] Figure 1 This is the SEM image of the hydrogel adhesive in Example 1.
[0030] Figure 2 This is a graph showing the rate performance test of a button cell made of the hydrogel adhesive in Example 1 at 0.1-1C;
[0031] Figure 3 This is a long cycle performance test of a button cell made of the hydrogel adhesive in Example 1 at 0.5C, wherein commercial CMC is used as a comparison sample. DETAILED DESCRIPTION
[0032] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.
[0033] As used herein, "and / or" includes the term of any and all combinations of one or more associated listed items. The terms used herein are only used to describe specific embodiments and are not intended to limit the present invention. As used herein, the singular forms "a", "an", "an" and "the" are also intended to include the plural forms, unless the context clearly indicates otherwise. It is further understood that "including", when used in this specification, specifies the stated features, integers, steps, operations, elements and / or compositions, but does not exclude the existence or addition of one or more other features, integers, steps, operations, elements, compositions and / or combinations thereof.
[0034] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. It is further understood that terms, such as defined in commonly used dictionaries, are interpreted in accordance with their meanings in the context of the relevant art and are not in an idealized or overly formal sense unless explicitly so defined herein.
[0035] The exemplary invention described herein may appropriately lack any one or more element limitations that are not specifically disclosed herein. Therefore, the terms "comprise", "include", "contain", etc. should be understood broadly and non-restrictively. In addition, the terminology used herein is used as a description, not a limitation, and it is unintentional to use these terminology expressions that do not include any equivalent characteristics, but only describe some of their characteristics, but various modifications are possible within the scope of the present invention according to the rights. Therefore, although the present invention has been specifically disclosed by preferred embodiments and optional features, the modifications disclosed herein to embody the changes of the present invention may be recorded by those skilled in the art, and such modifications and changes will be considered to be within the scope of the present invention.
[0036] A hydrogel adhesive comprises the following raw materials: a flexible hydrogel polymer, an alginate polymer, and a self-healing polymer, wherein the weight ratio of the flexible hydrogel polymer, the alginate polymer, and the self-healing polymer is (3.2-3.5):1:(3.2-3.5).
[0037] In some embodiments, the flexible hydrogel polymer includes any one or more of polyaniline, polypyrrole, and poly(3,4-ethylenedioxythiophene).
[0038] Specifically, flexible hydrogel polymers are hydrogel polymers with specific π-conjugated systems, such as polyaniline, polypyrrole, and poly(3,4-ethylenedioxythiophene); flexible hydrogel polymers have high conductivity, good mechanical properties, easy processability, and extraordinary biocompatibility, making them the best choice for hydrogels to construct three-dimensional cross-linked porous microstructures. Flexible hydrogel polymers have a unique organic and polymeric structure with a variety of chemical modification sites that can be integrated with the hydrophilic hydrogel network to pave a uniformly dispersed conductive path. The doping method based on flexible hydrogel polymers can use multifunctional crosslinkers (such as phytic acid, carbon dots, or borax) to introduce crosslinking, steric effects, and self-assembly capabilities, thereby releasing new functions to regulate morphology and physical / chemical properties.
[0039] More specifically, in the present application, polyaniline may be selected from CAS No. 25233-30-1;
[0040] The CAS number of polypyrrole is 30604-81-0;
[0041] Poly(3,4-ethylenedioxythiophene) CAS number is 126213-51-2, molecular formula is (C6H4O2S) n ;
[0042] In some embodiments, the alginate polymer includes any one or more of kelp gum, alginate, alginate and carboxymethyl cellulose salt. The alginate polymer can tightly connect silicon-based particles through chemical bonds, promote the formation of solid electrolyte interface film, and inhibit the decomposition of electrolyte.
[0043] In some embodiments, the self-healing polymer is polyacrylic acid, CAS number: 9003-01-4; polyacrylic acid is a hydrophilic weak electrolyte material with a high glass transition temperature. Elastomers based on polyacrylic acid have high mechanical strength. At the same time, the main chain of polyacrylic acid contains a large number of carboxyl groups, which can be converted into carboxylate anions under weak alkaline conditions to coordinate with metal ions, so that the elastomer has a certain self-healing property.
[0044] Specifically, polyacrylic acid with a carboxyl group (-COOH) is used as a counter ion for doping protonated imine groups (-NH2). The carbonyl group greatly enhances the solubility of polyaniline (PANI), polypyrrole (PPy) and poly(3,4-ethylenedioxythiophene) (PEDOT) in water, ensuring that both are evenly dispersed in the solvent.
[0045] The preparation method of the hydrogel adhesive comprises the following steps:
[0046] The flexible hydrogel polymer, the alginate polymer and the self-healing polymer are mixed according to the weight ratio, and a solvent and a cross-linking agent are added to react. After the reaction is completed, a hydrogel adhesive is obtained.
[0047] Specifically, the cross-linking agent is phytic acid, and the solvent includes any one or more of deionized water, ethylene glycol, ethanol and propylene glycol; the added volume (ml) of phytic acid is 0.5-1 times the weight (g) of the self-healing polymer, and the added volume (ml) of the solvent is 3-5 times the weight (g) of the self-healing polymer, and the dropping rate of phytic acid and solvent is stably added within 5 minutes.
[0048] In the present application, during the preparation process of the hydrogel adhesive, a cross-linking agent (such as phytic acid) tightly connects raw materials such as flexible hydrogel polymers, alginate polymers and self-healing polymers through the action of chemical bonds to form a stable three-dimensional cross-linked structure; the three-dimensional cross-linked structure makes the hydrogel adhesive have stronger mechanical strength and stability, and can resist deformation and damage under the action of external forces.
[0049] At the same time, during the reaction, the cross-linking agent can promote the formation of cross-linking points between the molecular chains of each component, thereby constructing a hydrogel network with a chain entangled foam structure. This network structure not only improves the conductivity and mechanical properties of the hydrogel, but also helps to inhibit the volume expansion of the Si-based negative electrode during the charge and discharge process, and improves the cycle stability and life of the battery. The role of the cross-linking agent is also reflected in enhancing the adhesion properties of the hydrogel adhesive. By optimizing the use of the cross-linking agent, a stronger bond can be formed between the hydrogel adhesive and components such as Si-based particles and conductive agents, thereby improving the overall performance and stability of the negative electrode.
[0050] More specifically, the solvent includes any one or more of deionized water, ethylene glycol, ethanol and propylene glycol.
[0051] In a third aspect, the present application provides a negative electrode, comprising the hydrogel adhesive described above, Si-based particles, and a conductive agent.
[0052] In a fourth aspect, the present application provides a method for preparing the negative electrode, comprising the following steps:
[0053] The hydrogel binder, Si-based particles and conductive agent are fully mixed to obtain a Si-based negative electrode slurry; the particle size of the Si-based particles is 2-3 μm, and the mass ratio of the Si-based particles, the conductive agent and the binder is 15:3:2; the conductive agent includes any one of conductive carbon black (SuperP), carboxyl carbon nanotubes, hydroxyl carbon nanotubes and amino carbon nanotubes;
[0054] The Si-based negative electrode slurry was coated on the non-smooth surface of the Cu foil, first dried at 60°C for 2 h, and then vacuum dried at 120°C for 12 h to obtain the negative electrode.
[0055] In a fifth aspect, the present application provides a lithium-ion battery comprising the negative electrode and electrolyte described above, wherein the electrolyte comprises ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate and additives, wherein fluoroethylene carbonate is the additive.
[0056] Example 1
[0057] The method for preparing the negative electrode comprises the following steps:
[0058] S1. Preparation of Si-based negative electrode slurry with hydrogel binder
[0059] Add polyaniline, polyacrylic acid and sodium alginate into 6 ml of deionized water, add 1 ml of phytic acid dropwise, and mix them evenly after 6 hours of vigorous stirring to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of polyaniline, polyacrylic acid and sodium alginate is 6.5:6.5:2, and the sum of the masses of polyaniline, polyacrylic acid and sodium alginate is 1 g;
[0060] Then, Si-based particles and conductive carbon black were added to the hydrogel binder (the mass ratio of Si-based particles, conductive agent and hydrogel binder was 75:15:10), and the mixture was vigorously stirred for 4 hours using a homogenizer to prepare a Si-based negative electrode slurry with a chain entangled foam structure.
[0061] S2. Coating and drying
[0062] The Si-based negative electrode slurry prepared in step S1 was coated on the rough surface of the Cu foil by gravure roller coating to prepare an electrode sheet with a coating thickness of 18 μm; the electrode sheet was first dried at 60°C for 2 hours and then vacuum dried at 120°C for 12 hours to obtain a Si-based negative electrode with a chain entanglement foam structure.
[0063] Comparative Example 11
[0064] In the preparation method of the negative electrode, in step S1, polyaniline, polyacrylic acid and sodium alginate are added to 6 ml of deionized water, 1 ml of phytic acid is added dropwise, and the mixture is stirred vigorously for 6 hours to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of polyaniline, polyacrylic acid and sodium alginate is 5:5:5, and the sum of the masses of polyaniline, polyacrylic acid and sodium alginate is 1 g;
[0065] The remaining steps are consistent with Example 1;
[0066] Comparative Example 12
[0067] In the preparation method of the negative electrode, in step S1, polyaniline, polyacrylic acid and sodium alginate are added to 6 ml of deionized water, 1 ml of phytic acid is added dropwise, and the mixture is stirred vigorously for 6 hours to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of polyaniline, polyacrylic acid and sodium alginate is 4:4:7, and the sum of the masses of polyaniline, polyacrylic acid and sodium alginate is 1 g;
[0068] The remaining steps are consistent with Example 1;
[0069] Example 2
[0070] The method for preparing the negative electrode comprises the following steps:
[0071] S1. Preparation of Si-based negative electrode slurry with chain entanglement foam structure
[0072] Add polypyrrole, polyacrylic acid and sodium alginate into 6 ml of deionized water, add 1 ml of phytic acid dropwise, and mix them evenly after 6 hours of vigorous stirring to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of polypyrrole, polyacrylic acid and sodium alginate is 6.5:6.5:2, and the sum of the masses of polypyrrole, polyacrylic acid and sodium alginate is 1 g;
[0073] Then, Si-based particles and carboxyl carbon nanotubes were added to the hydrogel binder (the mass ratio of Si-based particles, conductive agent and hydrogel binder was 75:15:10), and the mixture was vigorously stirred for 4 hours by a homogenizer to prepare a Si-based negative electrode slurry with a chain entangled foam structure.
[0074] S2. Coating and drying
[0075] The Si-based negative electrode slurry prepared in step S1 was coated on the rough surface of the Cu foil by gravure roller coating to prepare an electrode sheet with a coating thickness of 19 μm; the electrode sheet was first dried at 60°C for 2 hours and then vacuum dried at 120°C for 12 hours to obtain a Si-based negative electrode with a chain entanglement foam structure.
[0076] Comparative Example 21
[0077] In the preparation method of the negative electrode, in step S1, polypyrrole, polyacrylic acid and sodium alginate are added to 6 ml of deionized water, 1 ml of phytic acid is added dropwise, and the mixture is stirred vigorously for 6 hours to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of polypyrrole, polyacrylic acid and sodium alginate is 5:5:5, and the sum of the masses of polypyrrole, polyacrylic acid and sodium alginate is 1 g;
[0078] The remaining steps are consistent with Example 2.
[0079] Comparative Example 22
[0080] In the preparation method of the negative electrode, in step S1, polypyrrole, polyacrylic acid and sodium alginate are added to 6 ml of deionized water, 1 ml of phytic acid is added dropwise, and the mixture is stirred vigorously for 6 hours to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of polypyrrole, polyacrylic acid and sodium alginate is 4:4:7, and the sum of the masses of polypyrrole, polyacrylic acid and sodium alginate is 1 g;
[0081] The remaining steps are consistent with Example 2.
[0082] Example 3
[0083] The method for preparing the negative electrode comprises the following steps:
[0084] S1. Preparation of Si-based negative electrode slurry with chain entanglement foam structure
[0085] Poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate were added into 6 ml of deionized water, 1 ml of phytic acid was added dropwise, and the mixture was stirred vigorously for 6 hours to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate was 6.5:6.5:2, and the sum of the mass of poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate was 1 g;
[0086] Then, Si-based particles and amino carbon nanotubes were added to the hydrogel binder (the mass ratio of Si-based particles, conductive agent and hydrogel binder was 75:15:10), and the mixture was vigorously stirred for 4 hours by a homogenizer to prepare a Si-based negative electrode slurry with a chain entangled foam structure.
[0087] S2. Coating and drying
[0088] The Si-based negative electrode slurry prepared in step S1 was coated on the rough surface of the Cu foil by gravure roller coating to prepare an electrode sheet with a coating thickness of 20 μm; the electrode sheet was first dried at 60°C for 2 hours, and then vacuum dried at 120°C for 12 hours to obtain a Si-based negative electrode with a chain entanglement foam structure.
[0089] Comparative Example 31
[0090] In the preparation method of the negative electrode, in step S1, poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate are added to 6 ml of deionized water, 1 ml of phytic acid is added dropwise, and the mixture is stirred vigorously for 6 hours to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate is 6.5:6.5:2, and the sum of the masses of poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate is 1 g;
[0091] The remaining steps are consistent with Example 3.
[0092] Comparative Example 32
[0093] In the preparation method of the negative electrode, in step S1, poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate are added to 6 ml of deionized water, 1 ml of phytic acid is added dropwise, and the mixture is mixed vigorously for 6 hours to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate is 4:4:7, and the sum of the masses of poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate is 1 g;
[0094] The remaining steps are consistent with Example 3.
[0095] Example 4
[0096] The method for preparing the negative electrode comprises the following steps:
[0097] S1. Preparation of Si-based negative electrode slurry with chain entanglement foam structure
[0098] Polyaniline, polyacrylic acid and sodium alginate were added into a mixed solvent of 10 ml deionized water and ethanol (volume ratio of 6:4), 1 ml of phytic acid was added dropwise, and the mixture was stirred vigorously for 6 hours to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of polyaniline, polyacrylic acid and sodium alginate was 6.5:6.5:2, and the sum of the masses of polyaniline, polyacrylic acid and sodium alginate was 1 g;
[0099] Then, Si-based particles and hydroxyl carbon nanotubes were added to the hydrogel binder (the mass ratio of Si-based particles, conductive agent and hydrogel binder was 75:15:10), and the mixture was vigorously stirred for 4 hours by a homogenizer to prepare a Si-based negative electrode slurry with a chain entangled foam structure.
[0100] S2. Coating and drying
[0101] The Si-based negative electrode slurry prepared in step S1 was coated on the rough surface of the Cu foil by gravure roller coating to prepare an electrode sheet with a coating thickness of 21 μm; the electrode sheet was first dried at 60°C for 2 hours, and then vacuum dried at 120°C for 12 hours to obtain a Si-based negative electrode with a chain entanglement foam structure.
[0102] Comparative Example 41
[0103] Add polyaniline, polyacrylic acid and sodium alginate into a mixed solvent of 10 ml deionized water and ethanol (volume ratio of 6:4), add 1 ml of phytic acid dropwise, and mix them evenly after vigorous stirring for 6 hours to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of polyaniline, polyacrylic acid and sodium alginate is 5:5:5, and the sum of the masses of polyaniline, polyacrylic acid and sodium alginate is 1 g;
[0104] The remaining steps are consistent with Example 4;
[0105] Comparative Example 42
[0106] Polyaniline, polyacrylic acid and sodium alginate were added into a mixed solvent of 10 ml deionized water and ethanol (volume ratio of 6:4), 1 ml of phytic acid was added dropwise, and the mixture was stirred vigorously for 6 hours to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of polyaniline, polyacrylic acid and sodium alginate was 4:4:7, and the sum of the masses of polyaniline, polyacrylic acid and sodium alginate was 1 g;
[0107] The remaining steps are consistent with Example 4;
[0108] Example 5
[0109] The method for preparing the negative electrode comprises the following steps:
[0110] Preparation of Si-based anode slurry with chain entanglement foam structure
[0111] Add polypyrrole, polyacrylic acid and sodium alginate into 10 ml of a mixed solvent of deionized water and ethanol (volume ratio of 6:4), add 1 ml of phytic acid dropwise, and mix them evenly after vigorous stirring for 6 hours to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of polypyrrole, polyacrylic acid and sodium alginate is 6.5:6.5:2, and the sum of the masses of polypyrrole, polyacrylic acid and sodium alginate is 1 g;
[0112] Then, Si-based particles and carboxyl carbon nanotubes were added to the hydrogel binder (the mass ratio of Si-based particles, conductive agent and hydrogel binder was 75:15:10), and the mixture was vigorously stirred for 4 hours by a homogenizer to prepare a Si-based negative electrode slurry with a chain entangled foam structure.
[0113] S2. Coating and drying
[0114] The Si-based negative electrode slurry prepared in step S1 was coated on the rough surface of the Cu foil by gravure roller coating to prepare an electrode sheet with a coating thickness of 22 μm; the electrode sheet was first dried at 60°C for 2 hours, and then vacuum dried at 120°C for 12 hours to obtain a Si-based negative electrode with a chain entanglement foam structure.
[0115] Comparative Example 51
[0116] Add polypyrrole, polyacrylic acid and sodium alginate into 10 ml of a mixed solvent of deionized water and ethanol (volume ratio of 6:4), add 1 ml of phytic acid dropwise, and mix them evenly after vigorous stirring for 6 hours to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of polypyrrole, polyacrylic acid and sodium alginate is 5:5:5, and the sum of the masses of polypyrrole, polyacrylic acid and sodium alginate is 1 g;
[0117] The remaining steps are consistent with Example 5;
[0118] Comparative Example 52
[0119] Add polypyrrole, polyacrylic acid and sodium alginate into 10 ml of a mixed solvent of deionized water and ethanol (volume ratio of 6:4), add 1 ml of phytic acid dropwise, and mix them evenly after vigorous stirring for 6 hours to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of polypyrrole, polyacrylic acid and sodium alginate is 4:4:7, and the sum of the masses of polypyrrole, polyacrylic acid and sodium alginate is 1 g;
[0120] The remaining steps are consistent with Example 5;
[0121] Example 6
[0122] The method for preparing the negative electrode comprises the following steps:
[0123] S1. Preparation of Si-based negative electrode slurry with chain entanglement foam structure
[0124] Poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate were added into a mixed solvent of 10 ml deionized water and ethanol (volume ratio of 6:4), 1 ml of phytic acid was added dropwise, and the mixture was mixed evenly by vigorous stirring for 6 hours to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate was 6.5:6.5:2, and the sum of the masses of poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate was 1 g;
[0125] Then, Si-based particles and conductive carbon black were added to the hydrogel binder (the mass ratio of Si-based particles, conductive agent and hydrogel binder was 75:15:10), and the mixture was vigorously stirred for 4 hours using a homogenizer to prepare a Si-based negative electrode slurry with a chain entangled foam structure.
[0126] S2. Coating and drying
[0127] The Si-based negative electrode slurry prepared in step S1 was coated on the rough surface of the Cu foil by gravure roller coating to prepare an electrode sheet with a coating thickness of 19 μm; the electrode sheet was first dried at 60°C for 2 hours, and then vacuum dried at 120°C for 12 hours to obtain a Si-based negative electrode with a chain entanglement foam structure.
[0128] Comparative Example 61
[0129] Poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate were added into a mixed solvent of 10 ml deionized water and ethanol (volume ratio of 6:4), 1 ml of phytic acid was added dropwise, and the mixture was mixed evenly by vigorous stirring for 6 hours to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate was 5:5:5, and the sum of the masses of poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate was 1 g;
[0130] The remaining steps are consistent with Example 6.
[0131] Comparative Example 62
[0132] Poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate were added into a mixed solvent of 10 ml deionized water and ethanol (volume ratio of 6:4), 1 ml of phytic acid was added dropwise, and the mixture was mixed evenly by vigorous stirring for 6 hours to obtain a hydrogel adhesive with a chain entanglement foam structure; wherein the mass ratio of poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate was 4:4:7, and the sum of the mass of poly(3,4-ethylenedioxythiophene), polyacrylic acid and sodium alginate was 1 g;
[0133] The remaining steps are consistent with Example 6;
[0134] The Si-based negative electrodes in Examples 1-6 and Comparative Examples 11, 12, 21, 22, 31, 32, 41, 42, 51, 52, 61, and 62 were subjected to mechanical peeling test, AFM analysis, and swelling test, respectively, and the test results are recorded in Table 1;
[0135] The peeling test used a HY-0580 device (Shanghai Hengyi Testing Instrument Co., Ltd.) to measure the mechanical strength of the adhesive, and the peeling speed was 200 mm min -1 , the stripping width is 20mm and the length is 300mm;
[0136] The electrolyte absorption capacity of the adhesive is expressed by the swelling of the electrode. The specific test method is to immerse the electrode in the electrolyte for 48 hours. The mass of the electrode before immersion is W1, and the mass after immersion is W2. The swelling (S) calculation formula is S = (W2-W1) / W1*100%. The diaphragm is selected as polyethylene film (PE, Celgard 2500), and the electrolyte is selected as ethylene carbonate / dimethyl carbonate (EC / DMC=3 / 7) volume ratio and 5wt% fluoroethylene carbonate (FEC) 1M LiPF6.
[0137] Table 1
[0138]
[0139]
[0140] From the results of Examples 1-6 in Table 1, it can be found that the adhesive of the chain entanglement foam structure has the advantages of excellent mechanical strength, good fatigue resistance and good biocompatibility.
[0141] Moreover, compared with the adhesive of the commercial CMC system, the swelling rate of the adhesive of Example 1 is significantly higher; when absorbing an appropriate amount of electrolyte, the capacity of the active material itself is easier to release, and the chain entanglement network synthesized by the cross-linking reaction in the adhesive system of Example 1 itself has a loose and porous structure, which is beneficial to improving the ability to absorb electrolyte and fully releasing the capacity of the active material.
[0142] from Figure 1 It can be seen that by taking the SEM image of the electrode surface of Example 1, it can be clearly seen that Example 1 is firmly adhered to the SiO x The negative electrode is surrounded by a dense mesh structure, giving SiO x The negative electrode has ample expansion space, which effectively increases the battery cycle life.
[0143] The adhesive of the chain entanglement foam structure in Example 1 and the commercial adhesive carboxymethyl cellulose (CMC) were used to assemble button batteries for performance comparison. The positive electrode of the button battery was SiOx, the negative electrode was a lithium sheet, the electrolyte was 1 mol / L LiPF6 dissolved in a solvent of EC / DMC=3:7, and the battery test temperature was 25°C.
[0144] like Figure 2 As shown, at 0.1-1C, the cycle performance of Example 1 is stable, the battery rate tolerance is good, and the battery capacity can be restored to 1545.1 mAh g -1 In contrast, the commercial CMC rate performance is extremely poor. When the current increases from 0.1C to 1C, the battery capacity of both batteries continues to decay. The capacity of the commercial CMC decays to 100mAh g at 0.5C and 1C. -1 .
[0145] like Figure 3 As shown in the figure, at 0.5C, Example 1 exhibits good cycling stability, indicating that the internal chain entanglement structure of Example 1 effectively controls the SiO x The volume expansion of the electrode ensures the integrity of the electrode structure to a great extent. In contrast, the commercial CMC test performance is extremely poor, and the capacity of the battery has greatly decayed after only a few dozen cycles, indicating that the single hydrogen bond force of the commercial CMC is difficult to resist the SiO x Due to the huge physical stress generated by itself, the electrode structure collapses instantly and the battery short-circuits.
[0146] This shows that the chain entanglement dynamic chain formed in Example 1 can stabilize SiO x Electrode structure. It can maintain normal battery cycle even under high current and has excellent reversible capacity.
[0147] The raw materials or reagents used in the examples and comparative examples of the present invention are all purchased from mainstream manufacturers in the market. Those without indicating the manufacturer or concentration are all analytically pure raw materials or reagents that can be routinely obtained. As long as they can play the expected role, there is no special limitation.
[0148] The instruments and equipment used in this embodiment are all purchased from major manufacturers in the market, and there is no particular limitation as long as they can play the expected role. In this embodiment, if no specific technology or conditions are specified, the technology or conditions described in the literature in this field or the product instructions are used. The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention can also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.
Claims
1. A hydrogel adhesive, characterized in that: The invention comprises the following raw materials: a flexible hydrogel polymer, an alginate polymer and a self-healing polymer, wherein the weight ratio of the flexible hydrogel polymer, the alginate polymer and the self-healing polymer is (3.2-3.5):1:(3.2-3.5).
2. The hydrogel adhesive according to claim 1, characterized in that The flexible hydrogel polymer includes any one or any combination of polyaniline, polypyrrole and poly(3,4-ethylenedioxythiophene).
3. The hydrogel adhesive according to claim 1, characterized in that The alginate polymer includes any one or any combination of kelp gum, alginate, alginate and carboxymethyl cellulose salt.
4. The hydrogel adhesive according to claim 1, characterized in that: The self-healing polymer is polyacrylic acid.
5. The method for preparing the hydrogel adhesive according to claims 1-4, characterized in that: The following steps are involved: The flexible hydrogel polymer, the alginate polymer and the self-healing polymer are mixed according to the weight ratio, and a solvent and a cross-linking agent are added to react. After the reaction is completed, a hydrogel adhesive is obtained.
6. A negative electrode, characterized in that The invention comprises the hydrogel adhesive according to any one of claims 1 to 4 or the hydrogel adhesive prepared by the preparation method according to claim 5.
7. The method for preparing a negative electrode according to claim 6, characterized in that: The following steps are involved: The hydrogel binder, Si-based particles and conductive agent are fully mixed to obtain Si-based negative electrode slurry; The Si-based negative electrode slurry is coated on the rough surface of the Cu foil and dried to obtain the negative electrode.
8. The preparation method according to claim 7, characterized in that: The drying step is first drying at 60° C. for 2 h, and then vacuum drying at 120° C. for 12 h.
9. The preparation method according to claim 7, characterized in that: The particle size of the Si-based particles is 2-3 μm; the mass ratio of the Si-based particles, the conductive agent and the adhesive is 15:3:
2.
10. A lithium ion battery, characterized in that: The invention comprises the negative electrode according to claim 6 or the negative electrode prepared by the preparation method according to any one of claims 7 to 9.
Citation Information
Cited By
Conductive hydrogel adhesive with temperature phase change characteristic for fixing skin electrode
CN120944479A
Conductive hydrogel adhesive with temperature phase transition properties for securing epidermal electrodes
CN120944479B